The relationship between parental phubbing and bullying behavior in middle school students: the mediating role of family closeness and negative emotions - Ganggang Pang; Caixia Wang; Cheng Kang (BMC Psychology)
Abstract Purpose This study examined the mediating role of family closeness and negative emotions in the relationship between parental phubbing and bullying behavior in middle school students. Methods A survey was conducted on 1281 middle school students using the Parental Phubbing Scale, Family closeness Scale, Negative Emotion Scale, and Bullying Behavior Questionnaire. Results (1) Parental phubbing was significantly and positively related with bullying behavior in middle school students; (2) Parental phubbing was related with bullying behavior in middle school students through the separate mediating effects of family closeness and negative emotions, as well as their sequential chain mediating effect. Conclusions This study revealed the mechanism of parental phubbing on bullying behavior of middle school students, which can effectively reduce bullying behavior in schools by enhancing family closeness and improving students’ emotional state, and provides empirical evidence for the development of interventions.